Prevalence of Hypertension among the Bangladeshi Adult Population: A meta-analysis of Studies between 2004 and 2014 (Cardiovascular Journal, 2015)
Background: Hypertension has become a significant problem in many developing countries undergoing epidemiological transition from communicable to non-communicable chronic diseases. Previous studies covering up to 1999 reported a prevalence of ll.3% in the adult population of Bangladesh. Methods: We have searched National Institute of Cardiovascular Diseases (NICVD) Library and PubMed@ Resources Guide for published Hypertension prevalence studies between 2004 and 2014. A meta-analysis was conducted to estimate the prevalence of hypertension among the adult Bangladeshi population. We have considered population-based studies that had a clear definition of hypertension, and were conducted in adults (>18 years). We have marked seventeen articles, of which only six articles fulfill the selection criteria were included for the current analysis. Then the prevalence of hypertension and their 95% CIs for the individual studies were calculated by using the data presented. Finally a pooled estimate was obtained from six studies. Results: The pooled estimate for the prevalence of hypertension in 2972 adults was 20.88% (18.75% - 22.87%) which almost double than the previous estimated value. Conclusion: The meta-analysis clearly demonstrates the high burden of hypertension among the adult population of rural Bangladesh and underscores the importance of instituting screening for asymptomatic individuals with potentially harmful hypertensive disorder, especially in primary health-care settings to combat the growing epidemic of Noncommunicable Diseases. Large scale studies can be done including all the high risk population to represent the actual scenario of hypertension in Bangladeshi adult population. DOI: http://dx.doi.org/10.3329/cardio.v7i2.22251 Cardiovasc. j. 2015; 7(2): 104-107